Social cognition in adults with mild intellectual disability, dual diagnosis and typical development persons - Mastilo, Bojana (Specijalna edukacija i rehabilitacija, 2023)
Introduction. Social cognition is a multidimensional construct that encompasses higher-order cognitive processes used to process and interpret social information and successfully communicate with others. These processes include cognitive theory of mind, affective theory of mind, understanding of social norms, moral judgment and empathy. Objective. The aim of our study was to determine the differences in social cognition in adults with mild intellectual disability, dual diagnoses, and typical development paired chronologically, and to determine the relationship between age, gender and socio-cognitive abilities in all three groups. Methods. Our study included 122 participants, of whom 32 were with intellectual disability, 30 had dual diagnoses, and 60 were typically developing adults. The Edinburgh Social Cognition Test - ESCoT was used to assess social cognition, while the Mini Psychiatric Assessment Scale for Adults with Developmental Disorders, MINI PAS - ADD was used to confirm the presence of psychiatric symptoms in adults with developmental disabilities. Results. The obtained results showed that adults with mild intellectual disability had better performance in social cognition than adults with dual diagnoses, but worse than typically developing adults. Also, the research showed that in the subsample of typically developing participants, these abilities decreased with age, the abilities of affective theory of mind decreased with age in persons with intellectual disabilities, while no correlation was found between younger and older respondents in persons with dual diagnoses. Our research has not confirmed the relationship between gender and social cognition. Conclusion. By determining the development of social cognition in adults with intellectual disability and dual diagnoses, we gain insight into their adaptive functioning in everyday social interactions.
Keywords: social cognition; theory of mind; intellectual disability; dual diagnoses